Husserl’s Phenomenology of Validity - Susi Ferrarello (Rosenberg & Sellier, 2016)
What is a practical intention, particularly an evaluating intention? Are values representational states that work differently from epistemological truths? Are our perceptual experiences representational states? To simplify the inquiry, I will theoretically divide the questions into two groups: the former concerning the distinction between signitive and practical intention and the latter pertaining to the objectivity of a value. The texts I will refer to are Husserl’s Ideas and Analysis.